Design E-Consulting System Using the Waterfall Model - Fajar Daeng Bani; Bayu Prabowo Sutjiatmo (Jurnal Teknologi dan Manajemen, 2024)
Information technology is currently developing rapidly so that individuals, companies and government agencies can play a role in decision making. The current problem is the lack of optimal reporting on academic guidance activities for students and lecturers. Academic guidance is a process of assistance and assistance given to individuals in developing their academic potential. Academic guidance is given by academic supervisors to students in the academic field during the study period with the aim of providing assistance and advice to students in courses and providing continuous supervision for the smooth running of lectures. The role of technology is a strategic part in the implementation of education in achieving goals by systematically designing an e-consulting system using the waterfall model so that academic supervisors get evidence of concrete reports to report lecturer workload and then students get evidence of academic guidance reports as a requirement to take the final project. This case study explains how the implementation of academic guidance can be carried out and according to academic needs and users effectively by using the waterfall model in tertiary institutions under the ministry of industry Republic of Indonesia.